2015
DOI: 10.1093/bioinformatics/btv123
|View full text |Cite
|
Sign up to set email alerts
|

Automated benchmarking of peptide-MHC class I binding predictions

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
148
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(150 citation statements)
references
References 36 publications
1
148
1
Order By: Relevance
“…35,36,66 NetMHCpan was selected because it consistently performs as one of the best prediction tools across a wide array of alleles, and also provides predicted IC50 nM values for the complete set of common class I alleles considered here. 67,68 In addition to predicted affinity (IC50), NetMHCpan also provides a percentile score expressing the relative capacity of each peptide to bind each specific allele, compared to a universe of potential sequences of the same size. While newer versions of NetMHCpan are available, we focused on the 2.8 version as only for this implementation a length-rescaling model is available, as described by Trolle et al 40 Briefly, ligands from five common HLA class I alleles were eluted and the allele-specific length-distribution of ligands was determined.…”
Section: Methodsmentioning
confidence: 99%
“…35,36,66 NetMHCpan was selected because it consistently performs as one of the best prediction tools across a wide array of alleles, and also provides predicted IC50 nM values for the complete set of common class I alleles considered here. 67,68 In addition to predicted affinity (IC50), NetMHCpan also provides a percentile score expressing the relative capacity of each peptide to bind each specific allele, compared to a universe of potential sequences of the same size. While newer versions of NetMHCpan are available, we focused on the 2.8 version as only for this implementation a length-rescaling model is available, as described by Trolle et al 40 Briefly, ligands from five common HLA class I alleles were eluted and the allele-specific length-distribution of ligands was determined.…”
Section: Methodsmentioning
confidence: 99%
“…For a given HLA molecule and a given peptide length, several benchmarks have shown that binding predictions correlate well with measured binding affinities (14), and that peptides with high predicted affinity contain the vast majority of T cell epitopes (5, 6). This has allowed comprehensive mapping of epitopes in entire pathogens by focusing testing on a manageable number of top predicted binders, saving vast amounts of resources (712).…”
Section: Introductionmentioning
confidence: 99%
“…To summarize briefly, a neural network is trained to output the affinity of a given pMHC pair that has the MHC represented by pseudo sequences constructed from HLA residues in contact with bound peptides, which are poly morphic in known functional HLA-A, HLA-B or HLA-C alleles. Pan-specific tools, such as NetMHCpan 77 and NetMHCIIpan 78 , scored among the best performers, even compared to allele-specific approaches 79,80 . However, although several assessments and comparisons have been made in the past 79,81,82 , there are currently no recent independent benchmark studies that can be used to recommend specific tools.…”
Section: Phased Genotypesmentioning
confidence: 99%